2004
DOI: 10.2134/agronj2004.0742
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management in Nonirrigated Glyphosate‐Resistant and Non‐Resistant Soybean following Deep and Shallow Fall Tillage

Abstract: Effect of tillage in combination with varying weed management on weed populations in and yields from nonirriManagement inputs that maximize economic return from the early gated ESPS plantings has not been determined. plantings of soybean [Glycine max (L.) Merr.] in the midsouthernRedvine is a perennial, woody dicot vine that occurs extensive root system (Elmore et al., 1989a(Elmore et al., , 1989b. 4,4Ј-bipyridinium dichloride)] effectively remove top growth of perennial weeds, but have little effect on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
4
2
Order By: Relevance
“…These results indicate that use of PRE + POST vs. POST‐only weed management is not necessary for achieving highest yields and net returns with either non‐GR or GR cultivars grown either continuously or in rotation. This agrees with the findings of Gonzini et al (1999), Nelson and Renner (1999), Roberts et al (1999), Corrigan and Harvey (2000), Payne and Oliver (2000), and Heatherly et al (2003b)(2004). This affirmation of the superior cost effectiveness of POST‐only weed management in soybean meshes well with the underlying premise of POST‐only weed management in a GR soybean production system.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate that use of PRE + POST vs. POST‐only weed management is not necessary for achieving highest yields and net returns with either non‐GR or GR cultivars grown either continuously or in rotation. This agrees with the findings of Gonzini et al (1999), Nelson and Renner (1999), Roberts et al (1999), Corrigan and Harvey (2000), Payne and Oliver (2000), and Heatherly et al (2003b)(2004). This affirmation of the superior cost effectiveness of POST‐only weed management in soybean meshes well with the underlying premise of POST‐only weed management in a GR soybean production system.…”
Section: Discussionsupporting
confidence: 93%
“…Herbicides alone cannot provide adequate control of redvine and trumpetcreeper; thus, additional control tactics may be necessary by producers. Research conducted recently at the same location indicates that increased redvine presence in soybean is not associated with a yield decline (Heatherly et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redvine is more susceptible to cooler temperatures and shorter root segments compared with trumpetcreeper (Chachalis and Reddy 2005). Redvine control in this study was higher than that reported by Heatherly et al (2004), partly because of differences in experimental conditions. Plots were deeptilled twice in this study, compared with once in the study by Heatherly et al (2004).…”
Section: Resultscontrasting
confidence: 68%
“…One of the main problems with the refusal of conventional moldboard plowing is increasing the growth of weeds what, without any appropriate additional measures, leads to a decrease in the yield of cultivated plants [11]. Although deep tillage of 30 cm alone, with the same yield as compared with basic surface tillage, was ineffective against perennial weeds [12]. As for evaluation of the economic component of tillage methods, some authors say that minimal and zero tillage providing an average yield increase by 18% give lower average annual net income due to high costs of agricultural equipment and herbicides compared to conventional tillage [13].…”
Section: Introductionmentioning
confidence: 99%